Performance Appraisal, Reward And Punhisment Pengaruhnya Terhadap Kinerja Pegawai - Syaifullah, Chaidar (Universitas Sam Ratulangi, 2016)
Company and employees are two things that needed each other. If employees succeeded in carrying progress for the company, the advantage gained be plucked by both parties.For employees, success is actual potential self and opportunities to meet the life.For the company, success is a means of to growth and development company. Along with progress, companies often times ignoring about human resource management available. Results gathered in this research is together is the significant between performance appraisal, rewards and punishment of the performance of employees. Performance appraisal influential significantly of the performance of employees.Is the positive and welfare between rewards of the performance of civil servants and punishment significant of the performance of employees at PT. PLN (Persero) a region east kalimantan and north kalimantan berau area. Keywords : Performance Appraisal, Reward, Punishment, PT. PLN (Persero)